p53 expression and relationship with MDM2 amplification in breast carcinomas - BÜYÜKPINARBAŞILI, NUR; Buyukpinarbasili, NUR; GÜCİN, ZÜHAL; Gucin, ZÜHAL; ERSOY, YELIZ EMINE; Ersoy, YELİZ EMİNE; KADIOĞLU, HÜSEYİN; ILBAK, Ayca; Kadioglu, HÜSEYİN; Muslumanoglu, Mahmut (My University, 2016)
Carcinoma of the breast, like other malignancies, is a genetic disease with multiple genetic events leading to the malignant phenotype. p53 mutations are the most common genetic events in human cancer. Inactivation of p53 can be a result of mutation in gene sequence. One of the main structures that regulate p53 stabilization is MDM2. It suppresses p53 transcriptional activation by recognizing transactivation domain of p53. The loss of MDM2 function on p53 regulation results in deprivation of p53 tumor suppressor ability. Single nucleotide polymorphisms (SNP309 T->G exchange) or MDM2 amplification has been proposed to play a role in this issue. In the present study, our aim is to analyze p53 and MDM2 status and investigate their interactions in human sporadic breast carcinoma. The study groups were separated according to their molecular classifications. In each group, histologic type of the tumor, conventional prognostic parameters, p53, and MDM2 interactions were compared statistically. Tumors are divided into 4 subtypes due to estrogen and progesterone receptor status, HER-2, and Ki-67 proliferation index results. According to this classification, 23 cases are in the luminal A, 32 cases are in the luminal B, 15 cases are in the HER-2 positive, and 22 cases are in the triple-negative group, with a total of 92 cases. p53 expression is low in luminal breast carcinomas than HER-2 and triple-negative subtypes. MDM2 amplification frequency was found to be 5.4% in total. MDM2 gene amplification does not have a significant role in breast carcinogenesis, but other possible mechanisms may play a role in its inactivation. (C) 2016 Elsevier Inc. All rights reserved.